2017
DOI: 10.18203/2394-6040.ijcmph20171747
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on prevalence of obesity and its association with dietary habits among college students in Abha, Saudi Arabia

Abstract: Background: During the past few years there was a western influence in the kingdom of Saudi Arabia and as a result of it the eating habits among the male college students had rapidly changed which also increased the prevalence rate of overweight and obesity. Therefore the objectives of the study were 1) To determine the prevalence of overweight and obesity in a sample of male college students in Abha, Saudi Arabia. 2) To determine the relationship between the Student’s body weight and their eating habits. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
11
1
1
Order By: Relevance
“…1 Almost half of the students in this study (50.5%) ate regular meals; this finding was higher than those reported in other areas of Saudi Arabia, from the College of Health Sciences at Rass, Qassim University (36.7%) 20 and from Abha (31.0%). 21 Meanwhile, this finding was lower than that documented for Chinese (83.6%), 9 Lebanese (61.4%), 22 and Malaysian medical students (57.6%). 14 These habits need to be changed through educational programs aimed at enhancing healthy eating habits in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…1 Almost half of the students in this study (50.5%) ate regular meals; this finding was higher than those reported in other areas of Saudi Arabia, from the College of Health Sciences at Rass, Qassim University (36.7%) 20 and from Abha (31.0%). 21 Meanwhile, this finding was lower than that documented for Chinese (83.6%), 9 Lebanese (61.4%), 22 and Malaysian medical students (57.6%). 14 These habits need to be changed through educational programs aimed at enhancing healthy eating habits in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 63%
“…33 This study revealed that only 17.7% of the students ate meals on a daily basis without having snacks in between, while a majority (56.3%) had snacks between meals at least three times per week, and 26.5% had snacks daily. Daily consumption of snacks was also a common habit (35.96%) among the Saudi students in Abha, 21 and being a staple food in this region, dates were eaten by students typically around four times per week (29.21%). The findings of this study were higher compared to previous studies from various other countries, where fewer Syrian (53%), 34 Lebanese (53.20%), 22 and Malaysian (42.4%) 14 students consumed snacks regularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Alsharani MM et al in their study regarding dietary habits among college students in Saudi Arabia found that only 31% were regular in consuming meals and the rest 69% were irregular. 22 In the study conducted by AckuakuDogbe et al it was found that the overall breakfast skipping among the students was 71.92%. 15 In the study conducted by Bagordo et al 11% of students said that they skip the first meal of the day.…”
Section: Discussionmentioning
confidence: 97%
“…13 Alsharani et al in their study in Saudi Arabia found that 45% were normal weight, 28% were overweight and 20% were obese. 22 In a study conducted by Huang et al among the students of University of Kansas, USA it was found that 21.6% were overweight, 4.9% were obese and the rest had a normal BMI (N=736). 23 Racette et al conducted a study at Washington University in St.Louis, Missouri, USA and found that 5% were underweight, 76% normal weight, and 18% overweight (N=764).…”
Section: Discussionmentioning
confidence: 99%